Accidental Oral Injuries by Electric Toothbrush: A Report of Three Cases - Miki Yamada; Shunsuke Hino; Satoshi Nakamura; Yosuke Iijima; Takahiro Kaneko; Norio Horie (Case Reports in Dentistry)
In recent years, electric toothbrushes have become widespread. However, injuries caused by electric toothbrushes have rarely been reported. We describe three cases of oral penetrating injuries caused by electric toothbrushes. Case 1 occurred in a disabled boy while brushing due to unexpected movement. In Case 2, a mother using an electric toothbrush had fallen when bumped by her child. Case 3 involved a man using the toothbrush while taking a bath, who slipped in the bathtub. Cases 1 and 3 were using sonic toothbrushes, and Case 2 was using an oscillating-rotating toothbrush. Electric toothbrushes can cause oral penetrating injuries and infections in the same manner as manual toothbrushes. Prevention of oral trauma requires familiarity with the form and function of electric toothbrushes. Some room for improvement remains in optimizing the form of electric toothbrushes.